Analisa Pembelajaran Pembukuan Bendahara Melalui Aplikasi Hyperlink Excel - Kamil, Musthafa; Sabariah, Etika; Hartini, Dorit (CV. ITTC INDONESIA, 2024)
Book finance class treasurer very important to learning students on regulator fiancé the class with right passing write and croscek using ms excel to dashboard hyperlink. This tekhnic must be learning as development specialist knowledgement students MTS Darul Hikmah to add knowledg about tehknology information that relevamce by management class.. Facilty dasboards hyperlink from Ms excel can easy manner right, regular, thorough, and can easy croscek from write transaction finance according to faster with use Hyperlink